GE_GERICHTE A/3263/2023 vom 12. September 2023 - GE Cour de justice (2023)
ÉVACUATION DES DÉCHETS;CANTON;DOMICILE;AMENDE;INADVERTANCE MANIFESTE | LPE.31b.al1; LPE.31c.al1; LGD.17; LGD.43.al1; LGD.39.al1; LGD.43.al2